Circular RNA circSFMBT2 downregulation by HBx promotes hepatocellular carcinoma metastasis via the miR-665/TIMP3 axis - Haohan Liu; Yongcong Yan; Jianhong Lin; Chuanchao He; Hao Liao; Huoming Li; Zhenyu Zhou; Jie Wang; Kai Mao; Zhiyu Xiao (Elsevier, 2022)
Hepatitis B virus X protein (HBx) is considered as an oncogene in tumorigenesis and progression of hepatocellular carcinoma (HCC). In recent years, the important role of circular RNAs (circRNAs) in HCC has been increasingly demonstrated. However, the regulatory mechanisms of HBx on circRNAs remains largely unknown. In this study, we identified that a novel circRNA, circSFMBT2, was markedly downregulated by HBx. Low expression of circSFMBT2 was correlated with poor prognosis and vascular invasion. Functionally, overexpression of circSFMBT2 significantly inhibited HCC metastasis both in vitro and in vivo. The mechanism of circSFMBT2 was to as a sponge of miR-665, which is a negative regulator of tissue inhibitor of metalloproteinases 3 (TIMP3). However, HBx downregulated circSFMBT2 via the interaction with DExH-box helicase 9 (DHX9), which binds to flanking circRNA-forming introns. In conclusion, circSFMBT2, which is downregulated by HBx, acts as a tumor suppressor to inhibit tumor metastasis through the miR-665/TIMP3 axis. Our study suggests that circSFMBT2 could be a potential prognostic biomarker and therapeutic target for HCC.